Single and joint effects of natural and chemical stressors to the terrestrial isopod Porcellionides pruinosus - Morgado, Rui Guilherme da Costa (2015)
Environmental contamination and climate changes constitute two of the most serious problems affecting soil ecosystems in agricultural fields. Agriculture is nowadays a highly optimized process that strongly relies on the application of multiple pesticides to reduce losses and increase yield production. Although constituting, per se, a serious problem to soil biota, pesticide mixtures can assume an even higher relevance in a context of unfavourable environmental conditions. Surprisingly, frameworks currently established for environmental risk assessments keep not considering environmental stressors, such as temperature, soil moisture or UV radiation, as factors liable to influence the susceptibility of organisms to pesticides, or pesticide mixtures, which is raising increasing apprehension regarding their adequacy to actually estimate the risks posed by these compounds to the environment. Albeit the higher attention received on the last few years, the influence of environmental stressors on the behaviour and toxicity of chemical mixtures remains still poorly understood. Aiming to contribute for this discussion, the main goal of the present thesis was to evaluate the single and joint effects of natural stressors and pesticides to the terrestrial isopod Porcellionides pruinosus. The first approach consisted on evaluating the effects of several abiotic factors (temperature, soil moisture and UV radiation) on the performance of P. pruinosus using several endpoints: survival, feeding parameters, locomotor activity and avoidance behaviour. Results showed that these stressors might indeed affect P. pruinosus at relevant environmental conditions, thus suggesting the relevance of their consideration in ecotoxicological assays. At next, a multiple biomarker approach was used to have a closer insight into the pathways of damage of UV radiation and a broad spectrum of processes showed to be involved (i.e. oxidative stress, neurotoxicity, energy). Furthermore, UV effects showed to vary with the environment medium and growth-stage. A similar biomarker approach was employed to assess the single and joint effects of the pesticides chlorpyrifos and mancozeb to P. pruinosus. Energy-related biomarkers showed to be the most differentiating parameters since age-classes seemed to respond differently to contamination stress and to have different metabolic costs associated. Finally, the influence of temperature and soil moisture on the toxicity of pesticide mixtures was evaluated using survival and feeding parameters as endpoints. Pesticide-induced mortality was found to be oppositely affected by temperature, either in single or mixture treatments. Whereas chlorpyrifos acute toxicity was raised under higher temperatures the toxicity of mancozeb was more prominent at lower temperatures. By the opposite, soil moisture showed no effects on the pesticide-induced mortality of isopods. Contrary to survival, both temperature and soil moisture showed to interact with pesticides to influence isopods’ feeding parameters. Nonetheless, was however the most common pattern. In brief, findings reported on this thesis demonstrated why the negligence of natural stressors, or multiple stressors in general, is not a good solution for risk assessment frameworks.